Спектроскопічні особливості профілів ВКР підсилення в одномодових волокнах на основі кварцового скла - Serdeha, I. V.; Grygoruk, V. I.; Felinskyi, G. S. (Publishing house "Academperiodika", 2018)
The spectroscopic analysis of the frequency distribution of the amplification of optical radiation due to the Raman effect (Raman gain profile) in single-mode fibers based on silica glass has been carried out in the region of Stokes frequency shifts from 0 to 1400 cm−1. The Raman gain profiles are determined from the experimental spectra of spontaneous scattering for widespread fibers, namely for pure SiO2, GeO2, P2O5, and TiO2 doped fibers. The analytic expressions of the Raman gain profiles are given. They are obtained, by using the Gaussian decomposition by means of 11–12 modes, and the experimental profile is approximated with an accuracy of not less than 0.3%. The decomposition results are analyzed in terms of the fundamental oscillatory dynamics of molecular nanocomplexes in amorphous glass, as well as in the application aspect of the modeling of photonics devices. Examples of the proposed method applications are presented for the analysis of noise parameters of the fiber Raman amplifiers and for the generation bandwidth in fiber Raman lasers.